Innovation in creative technology: Academic and creative economy - Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir; Ahmad Rasdan Ismail; Suriatini Ismail (Elixir, 2015)
This paper reports the conceptual of innovation in creative technology in aspect of academic and creative economy. Creative industries have become the government's main agenda in achieving the vision 2020. The establishment of National Creative industry Policy is proof that the government is serious in their efforts to uplift the creative industry to a higher level. therefore, to ensure the government has met their mission, the education system must play their role to support the goal.